Heterosis and combining ability for quantitative traits in Canola (Brassica napus L.) using half diallel mating design (Journal of Oilseed Brassica, 2026)
In the year 2021-22, a set of 5 × 5 diallel crosses of canola were analyzed with their parents, to estimate heterosis as well as general combining ability (GCA) and specific combining ability (SCA). Observations on numerous quantitative characters were recorded. Almost all of the variables showed significant differences in GCA and SCA. The presence of both additive and non-additive gene interactions for the inheritance of distinct traits was revealed by the large magnitude of GCA and SCA effects. Parent IC-338967 was shown to be an excellent general combiner for seed yield, whereas BM 91 was shown to be a good earliness combiner. In the desirable direction, the high-ranking specific crosses for yield and its component were BM91 × EC338973, BM 91 × EC338976, BM9 1 × EC338977, EC338973 × EC338976, EC338973 × EC338967 and EC338977 × EC338967. Heterosis was observed in the F1 generation, and it differed by character. Most of the traits showed significant positive nature of heterosis when compared to a better parent and commercial check. For yield and associated parameters, all of the hybrids had a significant amount of heterobeltiosis. As a result, it might be further analyzed for detailed heterosis assessment or even in a breeding program to find the best cultivar/s.